Global Transcriptional Analysis Reveals Unique and Shared Responses in Arabidopsis thaliana Exposed to Combined Drought and Pathogen Stress - Gupta, Aarti; Sarkar, Ananda K.; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2016)
With frequent fluctuations in global climate, plants are exposed to co-occurring drought and pathogen infection and this combination adversely affects plant survival. In the past, some studies indicated that morpho-physiological responses of plants to the combined stress are different from the individual stressed plants. However, interaction of drought stressed plants with pathogen has not been widely studied at molecular level. Such studies are important to understand the defense pathways that operate as part of combined stress tolerance mechanism. In this study, Arabidopsis thaliana was exposed to individual drought stress, Pseudomonas syringae pv tomato DC3000 (Pst DC3000) infection and their combination. Using Affymetrix WT gene 1.0 ST array, global transcriptome profiling of leaves under individual drought stress and pathogen infection was compared with their combination. The results obtained from pathway mapping (KAAS and MAPMAN) demonstrated the modulation in defense pathways in A. thaliana under drought and host pathogen Pst DC3000 infection. Further, our study revealed ‘tailored’ responses under combined stress and the time of occurrence of each stress during their concurrence has showed differences in transcriptome profile. Our results from microarray and RT-qPCR revealed unique regulation of 20 novel genes exclusively during the stress interaction. This study indicates that plants exposed to concurrent drought and pathogen stress experience a new state of stress. Thus, under frequently changing climatic conditions each combination of stressor and their timing defines the plant responses and should thus be studied explicitly.